Risk assessment and safeguarding of lithium‐ion battery containing facilities. Issue 3 (30th September 2021) - Marszal, Edward; Bryan, Austin
Abstract: As the energy grid moves further toward renewable sources to generate the world's power requirements, energy storage becomes increasingly critical to infrastructure. Lithium‐ion batteries are an attractive option for such storage, with an energy density and cycling characteristics that provide advantages over other technologies. However, Li‐ion batteries also have several unique safety concerns due to the potential for thermal runaway, a self‐heating reaction, which can result in venting of both flammable and toxic gases and fire. This article explores the hazards associated with thermal runaways and discusses design considerations and requirements for systems intended to mitigate risk associated with such events.